Some parameters of economicvaluable signs of sort of soy in terms of left-bank Forest-Steppe zone of Ukraine - Шевніков, М. Я.; Галич, О. П.; Лотиш, І. І.; Міленко, О. Г. (Scientific Progress & Innovations, 2015)
As a result of study of sorts of soy the most productive sorts which in the conditions of left-bank Forest-Steppe zone combine the short period of vegetation and basic components of the productivity are selected. The weather terms of vegetation period substantially influenced on duration of interphase periods. The productivity of seed from one plant depended on the height of main stem, amount of the fertile knots, bobs and seed on a plant. Late-riped sorts had negative influence of height of attachment of lower bobs that showed up on the seed productivity.